1994
DOI: 10.1172/jci117048
|View full text |Cite
|
Sign up to set email alerts
|

A benign cultured colon adenoma bears three genetically altered colon cancer oncogenes, but progresses to tumorigenicity and transforming growth factor-beta independence without inactivating the p53 tumor suppressor gene.

Abstract: We describe the spontaneous progression of a colon adenoma cell line to tumorigenicity and growth factor independence. This system allows direct comparison of biologic stages of malignant progression with alterations of colon cancer suppressor genes and oncogenes. VACO-235, a human colon adenoma cell line, is at early passages nontumorigenic in the nude mouse, unable to grow in soft agar, growth stimulated by serum and EGF, and growth inhibited by TGF-beta. VACO-235 daughter passages 93 and higher have in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…5), which is consistent with the observations that CRC lines have reduced sensitivity to TGFβ1 (17) as a result of genetic changes, such as mutations in the TGFβ1RII receptor (associated with RER-positive lines such as HCT116) or SMAD4 (e.g., in HT29 cells) (27,28). Indeed, refractoriness to TGFβ1 is a feature of many human colorectal tumors (17,(46)(47)(48), and several other CRC lines (e.g., LS180, Lovo, SW480, SW949, and CaCo2) are even less responsive to TGFβ1 compared to HCT116 and HT29 cells (17). These observations suggest that the absence of TGFβ1-evoked SLC4A2 expression may be a more general CRC phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…5), which is consistent with the observations that CRC lines have reduced sensitivity to TGFβ1 (17) as a result of genetic changes, such as mutations in the TGFβ1RII receptor (associated with RER-positive lines such as HCT116) or SMAD4 (e.g., in HT29 cells) (27,28). Indeed, refractoriness to TGFβ1 is a feature of many human colorectal tumors (17,(46)(47)(48), and several other CRC lines (e.g., LS180, Lovo, SW480, SW949, and CaCo2) are even less responsive to TGFβ1 compared to HCT116 and HT29 cells (17). These observations suggest that the absence of TGFβ1-evoked SLC4A2 expression may be a more general CRC phenomenon.…”
Section: Discussionsupporting
confidence: 86%
“…The contribution of the plastic substrate as a transformation-inducible agent (Brand et al, 1975) has been reported, but it is not convincing because the mice implanted with plastic plates without adenoma cells did not develop tumors during 20 months of observation (Table 1). The spontaneous conversion during cell culture has previously been shown in experiments using other human colon adenoma cell lines (Paraskeva et al, 1992;Markowitz et al, 1994). However, malignant conversion constantly occurred at a high rate (65%) by implantation of the cells with plastic plates, whereas neither emergence of a tumorigenic subpopulation nor morphologic change was observed during in vitro passages of more than 200 times on the same plastic plate substrate (not shown).…”
Section: Inflammation Converts Adenoma Cells To Adenocarcinomamentioning
confidence: 59%
“…The Vaco411 cell line was originally established from a female patient with a villous colonic polyp with carcinoma in situ (Markowitz et al, 1994;Wang et al, 1995). Vaco411 cell culture and selection of independent 6TG resistant mutants were performed essentially as described (McBain et al, 1984;.…”
Section: Cell Culture and Selectionmentioning
confidence: 99%